PENGARUH LIKUIDITAS, LEVERAGE, DAN ARUS KAS TERHADAP FINANCIAL DISTRESS - Jennifen Wijaya; Rousilita Suhendah (Jurnal Paradigma Akuntansi, 2026)
The goal of this study is to collect empirical information regarding the effect of liquidity, leverage, and cash flow on financial distress. This study used consumer cyclicals sector companies listed on the IDX in 2019-2021. Samples were selected by purposive sampling method and the data used were 133 data. The obtained data was processed with the E-Views 12 application. According to the study, liquidity has a significant positive effect on financial distress, leverage has a significant negative effect on financial distress, while cash flow has a significant positive effect on financial distress. The study implies that liquidity, leverage, and cash flow influence the decisions of company management, investors, and creditors.